Propagation and scattering of APM in the piezoelectric plate with periodically corrugated surphaces - BOGUCKI, D. (Archives of Acoustics, 1995)
Bragg reflection of acoustic plate modes (APM) in piezoelectric plate with periodically grooved surfaces is analysed. Reflectional mode conversion and phenomena of APM propagation along the grooves are also taken into account. Influence of phase shift between the grooves on dispersion relations is also analysed. Presented results may be applied in the analysis of APM sensors and signal processing devices.